The association of sociodemographic and social capital with self-rated health: a microdata analysis of North Sumatera 2021 - Lubis, Sri Novita; Ronoatmodjo, Sudarto; Martha, Evi; Besral, Besral (International Journal of Public Health Science (IJPHS), 2025)
Current research suggests a possible connection between social capital and its effect on self-reported health. However, this relationship has not been extensively studied in urban and rural regions of Indonesia. This research aimed to evaluate the differences in sociodemographic factors, social capital, and self-rated health between rural and urban populations and to identify sociodemographic and social capital elements related to self-rated health in the urban and rural areas of Sumatra Utara Province, Indonesia. This study makes use of secondary data from the Happiness Level Measurement Survey Report 2021. A two-stage, one-phase sampling method was employed for sample selection. The Chi-square test was utilized to examine the distribution of factors related to respondents in both urban and rural settings. Multivariable Cox regression analysis was conducted to determine associations with self-rated health. Our findings indicate that rural inhabitants exhibit a higher rate of poor self-rated health compared to their urban counterparts (p-value<0.001). Significant differences were observed between urban and rural areas in terms of sex, education, trust, social participation, and feelings of safety. The multivariable Cox regression analysis revealed that being younger, having higher education, possessing greater trust, and engaging in high social participation was associated with a lower risk of poor self-rated health for both urban and rural residents. Consequently, trust and social participation could reduce the occurrence of poor self-rated health.